Factors affecting the happiness - KIM, Donghwan (KDI School, 2015)
Traditionally, happiness used to be recognized as having a positive relationship with the income level. However, the income level may not be the only factor which affects one’s happiness. The survey conducted by World Values Survey (WVS) asks two questions related to happiness and the results are converted into index by Inglehart. This paper adopts the index to research the linkage between happiness and other variables: GDP per capita, tertiary school enrollment ratio, urbanization level and car ownership rate. The results show that GDP per capita and urbanization level has a positive relationship with happiness states. On the other hand, tertiary school enrollment ratio negatively affects happiness. In the case of 16 countries in OECD, car ownership rate and urbanization level negatively affect happiness. Koreans have relatively a low level of happiness than other OECD countries do. This paper suggests the evidences that high tertiary school enrollment ratio and high urbanization level may be the causes of it.
Thesis(Master) --KDI School:Master of Public Policy,2015